Wine & conversation - Lehrer, Adrienne (New York ; Oxford : Oxford University Press, 2009)
The world of wine vocabulary is growing alongside the current popularity of wine itself. The question is, what do these words mean? Can they actually reflect the objective characteristics of wine, and can two drinkers really use and understand these words in the same way?
Previous ed.: Bloomington: Indiana University Press, 1983.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Semantics; Wine tasting -- Terminology; Conversation